Are dedicated mutual fund pension products able to outperform traditional pension funds? - Dudziak, Sebastian (2017)
More and more retirees are given the choice to allocate their pension investments with either their traditional employer-based pension plan or with mutual funds. Due to these developments, mutual funds increasingly provide pension products. This master thesis examines the performance difference between 78 U.S. dedicated mutual fund pension products (DMFPPs) and six U.S. traditional defined contribution funds. Performance is measured relative to style-adjusted benchmarks and is taking the fund’s cost component into account. Applying a single-factor and multi-factor model, I find that dedicated mutual fund pension products, on average, significantly underperform compared to traditional defined contribution funds. I will interpret the findings in the context of the agency cost debate, where mutual funds are more exposed to hidden costs than pension funds and extend the interpretation with the help of the fund value maximization and public choice theory. An equilibrium view concludes the thesis, where sophisticated investors, with time and skill, can find a more suitable investment with DMFPPs than with their traditional defined contribution plan